A new interferometric/polarimetric setup for plasma density measurements in compact microwave-based Ion Sources. (12th October 2017) - Torrisi, G.; Naselli, E.; Mascali, D.; Castro, G.; Celona, L.; Sorbello, G.; Gammino, S.
Abstract: A K-band (18.526.5 18.5÷26.5 GHz) microwave interferometry/polarimetry setup, based on the Frequency-Modulated Continuous-Wave (FMCW) method, has been developed at INFN-LNS under the VESPRI project. The interferometer has been proven to provide reliable measurements of the plasma density even in the extreme unfavorable conditionsλ_pL_pL_c λ p ≃ L p ≃ L c, beingλ_p λ p, L_p L p andL_c L c the probing signal wavelength, the plasma dimension and the plasma chamber length respectively. The VESPRI setup has been therefore upgraded with a rotating polarimetric system based on waveguide OMTs (OrthoModeTransducers) for the measurement of the magnetoplasma-induced Faraday rotation. An analysis method has been developed on purpose in order to discriminate the polarization plane rotation due to the plasma only, excluding the effects of the cavity resonator which represents the primary error source on phase angle measurement. Results about the first collected data, showing a significative agreement of the plasma-induced polarization plane rotation with the well-knownλ^2 λ 2 law, are hereby presented. The developed method will be a powerful tool for probing plasmas in very compact magnetic traps such as Electron Cyclotron Resonance Ion Sources.